Simulation on Hip Implant Using Finite Element Method - Amar Jauhari, Amar Reezlan; abdullah, haslina (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Hip implant is used to replace damaged bone on hip joint. The stem design is important since it will influence the performance of hip arthroplasty. In this study, simulations has been performed to investigate the effect of different geometry of implant to the stress distribution and displacement magnitude using the finite element method. The femoral bone was constructed using scan topography while the implant was from CAD software. In this study, there are three types of implant designs have been constructed which is stem without feature, stem with flute and stem with fin design. Then, Abaqus software has been employed to perform the analysis of stability and stress distribution. A hip implant was inserted into the femoral bone in Finite Element Method software and a simulation of displacement and stress distribution was conducted under walking conditions. Based on the simulation, it has been found that the fin feature developed the lowest displacement magnitude and stress distribution which are 0.07 µm and 58.81 Pa. As conclusion, adding additional feature to the implant would improve the implant’s stability while also experiencing less stress distribution.